Karakteristik Pengeringan Jamur Tiram (Pleurotus ostreatus var. florida) Menggunakan Pengering Tipe Fluidized Bed Drier - Tjahja Muhandri; Sarah Diana Yulianti; Elis Nina Herliyana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
The current practice for improving the quality and for ease handling of the oyster mushroom is drying. The drawback of this process results in dark color of the mushroom once it is dried. This color quality reduction wascaused by an unappropriate handling before drying and an over process of the drying. Thus, the objective of the research was to determine the most suitable model for drying rate of the mushroom and the best pre-treatments before drying. In this research, the influence of six pre-treatments before drying (1) control/without any pre-treatment, (2) washed using water, (3) blanching, (4) blanching followed by immersion in sodium metabisulphite solution, (5) blanching using a sodium metabisulphite solution, and (6) soaking in sodium metabisulphite solution, followed by blanching, on the quality of the mushroom (rehydration behavior) was elucidated. Those six samples were subjected to drying process using fluidized bed drier at 60 °C with airflow rate between 0.619 and 0.839 m/s until the samples reached equilibrium moisture content. The equilibrium moisture content was achieved after drying process of the mushroom from 270 to 330 minutes. Results indicated that Lewis model more suitable than Page model for prediction of the mushroom drying rate. Results also showed that the control/without any pre-treatment before drying and sample with washed using water were the best pre-treatments before drying resulted in the highest rehydration ratio with the short time of 150 minutes to reach the moisture content of 12%.ABSTRAKProses pengeringan jamur tiram (Pleurotus ostreatus) dilakukan untuk meningkatkan mutu dari jamur tiram dan mempermudah penanganannya. Penurunan mutu yang terjadi ketika jamur tiram dikeringkan adalah warna jamur yang coklat gelap dan tidak disukai konsumen. Kondisi ini terjadi karena penanganan sebelum pengeringan yang tidak tepat serta proses pengeringan yang terlalu lama. Penelitian ini dilakukan untuk mengetahui persamaan laju pengeringan jamur tiram, prediksi waktu pengeringan dan perilaku rehidrasinya. Jamur tiram diberi enam perlakuan yang berbeda yaitu (1) kontrol, (2) dicuci air bersih, (3) blansir, (4) blansir yang dilanjutkan dengan perendaman dalam natrium metabisulfit, (5) blansir dalam larutan natrium metabisulfit, dan (6) perendaman dalam larutan natrium metabisulfit yang dilanjutkan dengan blansir. Pengeringan dilakukan dengan fluidized bed dryer pada suhu 60 °C dan kecepatan udara pengering yang berada pada kisaran 0,619 m/detik hingga 0,839 m/detik sampai sampel mencapai kadar air kesetimbangan. Kadar air kesetimbangan (moisture equilibrium) dicapai setelah pengeringan selama 270 - 330 menit. Hasil pengujian menunjukkan bahwa model Lewis lebih sesuai dibandingkan dengan model Page untuk memprediksi laju pengeringan jamur tiram. Sampel jamur tiram tanpa perlakuan dan jamur tiram dengan perlakuan pencucian tanpa blansir merupakan sampel terbaik dengan waktu untuk mengeringkan hingga mencapai kadar air 12% adalah 150 menit dan rasio rehidrasi yang lebih tinggi dibandingkan sampel lainnya.